(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Poultry is a rapidly growing industry in India. Poultry meat eggs are a great source of vitamins micro nutrients that add to human diet as a valuable portion. The Indian Poultry Industry is estimated to be five thousand years old but has gained traction over the last four decades. Broilers are able to survive on many forms of diets, but perform well in diets made up of low-fiber grains easily digestible sources of protein. The broilers’ growth rate is known as the most significant economic feature in the broiler industry. Poultry feeds have been found adulterated with hormones, antibiotics, dioxine and other chemicals either deliberately, or from malpractice, or from sloppy manufacturing practices. Deficiency of a particular nutrient in the ration which is generally unnoticed by the farm owners causes major effects on production.